Effect of electrode interfaces on peak-drift switching current of PZT thin films. Issue 3 (15th February 2019) - Zhang, Qicheng; Geng, Wenping; Zhang, Jing; Qiao, Xiaojun; Chen, Xi; Fan, Xueming; Chou, Xiujian
Abstract: In this study, we investigated the impact of electrodes on the structural, crystal orientation, and electrical characteristics of lead zirconate titanate [Pb(Zr0.52 Ti0.48 )O3, PZT] thin films, that were deposited on Pt, Au, and LaNiO3 (LNO) electrodes through sol-gel processes. The peak voltage, that is, the voltage corresponding to the maximum switching current point, was developed to depict the novel peak-drift electric characteristics in ferroelectric thin films. It increases in the positive ferroelectric peak voltage, and decreases in the negative peak voltage with an increase in the driving voltage amplitude. Based on space-charge-limited bulk conduction, we evaluated the peak-drift phenomenon, Schottky contact and their influences on the switching current. When polarization orientation is reversed, the Schottky contact disappears at one side of the PZT/electrode, and forms at the other side synchronously. Our results indicate that the formation of a Schottky contact affects the shape of the switching curves, and its disappearance influences the magnitude of the current characteristics.